STEREOTIP POTRET PERILAKU PROFESI AKUNTAN DALAM SINEMATOGRAFI SESUAI DENGAN KODE ETIK PROFESI AKUNTAN - Darin Farah Nabilah; Bambang Tjahjadi (Politeknik Ganesha Medan, 2023)
The image of the accounting profession has been stereotyped in various visual and social media. Stereotypes strengthen the positive and negative characteristics of the accountant's own perceptions as well as the perception of public opinion in viewing the accounting profession. The research aim is to understand how the image of accountants is portrayed by the media as stated by Honorio et al. (2022) and stereotypes related to the image of an accountant found in the films The Accountant (2016), Tooi Bigltoi Fail (2011), Wanted (2008), The Dark Knight (2008), and Rock&Rolla (2008). The theory used was social representation and stereotypes related to the image of the accounting profession in a film. A qualitative writing method with a literature study approach used to find references regarding accountant stereotypes, as well as their representation in cinematographic productions by analyzing selected films. The results of the research show that visual media plays a bigger role in reinforcing current stereotypes, through the role of accountants in film production. Demystification of several stereotypes in the character of accountants began to be more diverse, no longer represented negatively. Characteristics such as courage, intelligence and credibility are predominant among other characters. Nevertheless, the characteristics raised are not used in accordance with the accounting professions code of ethics. Research contributes to the explanation of distortions involving the image of accountants in relation to what is depicted in the film, which still does not reflect the disclosure by the film and changes the negative image of the accounting profession from the public view. Subsequent research suggests analyzing in more detail from various aspects and can answer questions about professional ethics to generate greater visibility and interest for accounting professionals in the future. This research provides novelty related to the research field of the accounting profession in the world of cinematography.